2015
DOI: 10.1080/19443994.2015.1065442
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Remazol Brilliant Blue adsorption process from aqueous solutions using multi-walled carbon nanotube

Abstract: A B S T R A C TThis work aimed to determine the optimum conditions in order to reach the maximum remazol brilliant blue (RBB) removal and maximum adsorption capacity (uptake) in the sorption process from aqueous solution using multi-walled carbon nanotube (MWCNT). Three factors including initial RBB concentration, initial pH, and initial amount of MWCNTs were optimized using response surface methodology at equilibrium time 15 min. Optimized conditions were RBB concentration 8 × 10 −2 mmol/L, initial pH 4.3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Hence, the linearized form of kinetic relations was employed. The linearized equations can represent the following (Equation (5)–(8)) (Arab Markadeh et al., 2016; Hossini et al., 2016; Moussavi et al., 2013) …”
Section: Resultsmentioning
confidence: 99%
“…Hence, the linearized form of kinetic relations was employed. The linearized equations can represent the following (Equation (5)–(8)) (Arab Markadeh et al., 2016; Hossini et al., 2016; Moussavi et al., 2013) …”
Section: Resultsmentioning
confidence: 99%
“…Yan et al treated methylene blue dye by adsorption onto single‐walled carbon nanotubes and single‐walled carbon nanotubes modified with hydroxyl groups, confirming that charge‐transfer and hydrophobic interactions occurred during the adsorption process 49 . Markadeh et al optimized the removal of remazol brilliant blue onto multiwalled carbon and reported a removal efficiency of 69.06% and 1.1 × 10 −2 mM/g 50 . Shabaan et al investigated multiwall carbon nanotubes for adsorption of various dyes, including cationic and anionic dyes, and found removal percentages of 97.2% and 98.7%, respectively 47 .…”
Section: Introductionmentioning
confidence: 98%
“…49 Markadeh et al optimized the removal of remazol brilliant blue onto multiwalled carbon and reported a removal efficiency of 69.06% and 1.1 Â 10 À2 mM/g. 50 Shabaan et al investigated multiwall carbon nanotubes for adsorption of various dyes, including cationic and anionic dyes, and found removal percentages of 97.2% and 98.7%, respectively. 47 Qu et al…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there have only been a few published studies using this material. These studies have included the removal of antibodies and integration of biotechnology and ND , and its application as an adsorbent to remove acid orange 7 , eosin Y , metanil yellow , methylene blue , and remazol brilliant blue . There has only been one study that examined the potential of ND as a photocatalyst .…”
Section: Introductionmentioning
confidence: 99%